Effect of northeast monsoon on copper speciation at Pulau Perhentian, Terengganu, Malaysia - Godon, Edrianna (2017)
Copper (Cu) speciation was studied in the seawater at Pulau Perhentian, Terengganu, Malaysia in two different seasons, the pre- and post-Northeast monsoon. The existence of organic Cu (II) complexing ligands were determined by the application of CLEAdCSV to determine Cu bioavailability and toxicity in the area. The existence of organic ligands (CuL) in the area helps to keeps the solubility of Cu and maintains its concentration under the toxicity level. The development method of CLE-AdCSV for Cu(II) speciation was optimized by analysing the seawater samples collected from Pulau Perhentian. Multiple series of sampling were carried out in pre- and post-monsoon season to identify the possible effect of the Northeast monsoon to the Cu(II) speciation in the area. The profile of seawater samples was analyzed from selected stations at Pulau Perhentian, Terengganu for Cu(II) speciation determination in order to determine the concentration level of Cu(II) in dissolved seawater. The analysis showed that >99.5% of total dissolved Cu (dCu) was bound to Cu (II) complexing ligands in this area. The ratio of CuL/dCu was analysed to see the ligand distributions, which showed their saturation rate with dissolved Cu. For both Nov 2015 and 2016, the CuL/dCu ratio showed low ratio (1.00-1.90, 1.00-1.20) in open ocean (St. 1 and St. 2), and varied ratios were observed in near-shore stations at St. 3, St. 4 and St. 5 (1.10-4.30). Meanwhile for both April 2016 and 2017, the ratios were in low ranges (1.02-2.31, 1.00-1.60), especially in April 2017. This finding indicated a saturated Cu-ligand complexation in the area. The concentration of natural organic Cu(II)-ligand binding (CuL) and its conditional stability constant (Log K’CuL) in each sample was determined by using salicylaldoxime (SA) as competitive ligand. Our present data indicated the presence of strong natural organic Cu(II) complexing ligands in our seawater samples. Its distribution was similar to the dissolved Cu (dCu) throughout the water column, where the concentrations increased from the surface (3 m) to the middle layer (15m), before decreasing at the bottom layer. The Log K’CuL was more than 12.00 throughout the water column and indicated the presence of strong natural organic ligands in our study area. Preliminary data for Cu speciation in pre- and post-Northeast monsoon at Pulau Perhentian for two years (2015/2016 and 2016/2017) were presented here. All the results observed in saturation rate, complexation percentage, and the conditional stability constant, Log K’CuL and the pCu data suggested that the dissolved Cu in the study area are taken up by marine organisms, thus preventing the free Cu2+ ions to be produced. The complexing capacity of the species in the area were also highlighted in the results, which gave an indication of the ability of the organisms to absorb dissolved Cu and render it non-toxic, by complexing with dissolved Cu. In addition, the presence of dominant diatoms species might had also influence Cu bioavailability in the area. This initial study on Cu(II) speciation has suggested that more than 99% of dissolved Cu was complexed to the natural organic ligands which prevents the toxicity of Cu(II) to the marine organisms.